Irrigation in southern Africa: success or failure - Mutiro, J.; Lautze, Jonathan F. (Wiley, 2015)
Despite widespread recognition of the importance of irrigation development in southern Africa, no comprehensive examination exists on the performance of past irrigation schemes in the region. This paper systematically examines existing literature on irrigation schemes in southern Africa in order to: (i) determine the proportion that can be considered successful; and (ii) identify and rank factors that explain variation in performance. The results indicate that some 59% of irrigation schemes in southern Africa can be considered successful. Factors associated with successful performance include: management style, irrigation method, crop mix, type of financier and geography. The levels of success identified through this review validate calls to increase the irrigated area in southern Africa. These results nonetheless highlight opportunities to strengthen the way in which future irrigation schemes are undertaken. In particular, these results may call for increased use of sprinkler irrigation and reduced use of flood irrigation with pumping. The results also suggest more investment could be channelled into schemes focused on maize–vegetable crop rotations and sugar cane, and caution applied to government management of schemes.